Analysis of factors affecting the acceptance or use of e-wallet in Jakarta - Indry Aristianto Pradipta; Meisy Tresia (Journal of Economics and Business Letters, 2021)
Technology is developing rapidly and has a big impact in all aspects of the world. One of them is financial technology (fintech). Fintech e-wallet allows us to make payments using only mobile phones. Indonesia is one of the fastest digitizing countries that has started to take advantage of this new technology. However, the penetration rate still tends to be low. Fintech in Indonesia is still growing and competing with several fintechs that continue to emerge. The purpose of this study was to determine the factors that influence the acceptance or use of e-wallet. Methods of data collection using a questionnaire distributed to 200 respondents who have made payments using e-wallet and are domiciled in Jakarta. The analytical method used is structural equation modeling (SEM). The results showed that perceived usefulness and perceived ease of use had a positive and significant impact on attitudes toward using, and perceived usefulness and attitudes toward using had a positive and significant impact on behavioral intention to use.